Angle of Arrival Estimation Using Cholesky Decomposition - Saleh O. Al-Jazzar (International Journal of Antennas and Propagation)
An angle of arrival (AOA) estimator is presented. Many applications require accurate AOA estimates such as wireless positioning and signal enhancement using space-processing techniques. The proposed AOA estimator depends on the Cholesky decomposition of the received signal autocorrelation matrix. The resultant decomposed matrices are used to modify the crosscorrelation matrix of the received signals at the antenna array doublets. The proposed method is named the Cholesky-decomposition-based-AOA (CDBA) estimator. In comparison with the TLS-ESPRIT algorithm which utilizes the eigenvalue decomposition (EVD) of the received signal autocorrelation and crosscorrelation matrices, the CDBA method has better performance than the TLS-ESPRIT algorithm especially in low signal-to-noise-ratio (SNR) cases. Simulations for the proposed CDBA method are shown to assess its performance.